Railway photography and technology: analysis of the photographic record of Brazilian railway in the 19th century - Oliveira, Eduardo Romero De [UNESP] (Universidade Estadual Paulista Julio de Mesquita Filho, 2019)
The purpose of this text is to examine some sets of photographs about railway companies in Brazil, in order to highlight the potential of this type of iconographic material, not as artistic documentation but also technological documentation. We deal in particular with a collection of 6,000 photographs gathered by companies such as Companhia Paulista, Companhia Mogiana and Estrada de Ferro Sorocabana, which was deposited in the Museu da Companhia Paulista, in Jundiaí. These images were cataloged in 2014 by the RFFSA Inventory and IPHAN - within the attributions established to them by Law 11483/2007 - and then transferred to the Public Archive of the State of São Paulo. Although some images eventually had aesthetic quality, our first hypothesis is that the main reason for its production seems to have been technical: record of rolling stock or the evolution of construction work; therefore, this would be a routine activity in the companies that would explain the great volume of photographic material still existing. Secondly, we believe that the same material could be dealt with from the historical perspective of the technique and technology as an expression of technical-scientific knowledge and, often, by rules of machine representation and geographical space - although the pictorial tradition is not absent. This would demonstrate a potential for analysis of this type of iconographic material, where an interpretation proposed by the history of technology may not only enrich or complement studies of the history of photography, but also explore the importance of visual representation in technical-scientific knowledge.
Keywords: photography; railway; history of technology; public works; history of engineering